Analysis of Pulsatile Flow in Elastic Artery (Global Journal of Science Frontier Research, 2014)
In this paper, we have considered a Pulsatile flow in an elastic arterial tube and witnessed the efforts on the flow due to elasticity of the tube. The expression for "Volumetric flow rate" and "impedance of n th harmonic" have been found. Conclusions have been drawn with the aid of graphs. MATLAB software has been used for sketching graphs.
Keywords: elastic artery; shear stress; radial stress